Labour Supply Incentives in Alternative Tax and Transfer Schemes: A Diagrammatic Introduction - John Creedy (New Zealand Government, The Treasury, 2003)
The aim of this paper is to illustrate some of the complexities involved in modelling the incentive effects of taxes and transfers, using only basic diagrammatic methods. It describes a range of diagrams which are helpful in thinking about the design of tax and transfer systems and their potential effects on labour supply behaviour. Emphasis is given to the role of highly nonlinear budget constraints and the resulting wide range of labour supply responses.
Keywords: H31; 330; Labour supply; budget constraints; taxes and transfers